UNDERSTANDING OF MOTHERS' GROWTH PEMAHAMAN TUMBUH KEMBANG BALITA PADA IBU TERHADAP STATUS GIZI, LAMA PEMBERIAN ASI DAN MP ASI MENUJU REMAJA SEHAT DESA TANGGERAN SRUWENG: Tumbuh Kembang Balita Mp-ASI - ito, Marsito; Diah Astuti Ningrum; Ning Iswati; Rina Saraswati (PENA NURSING, 2025)
Understanding the growth and development of toddlers and nutritional status, breast milk and breast milk in mothers requires increased knowledge. So far, many mothers of toddlers don't know what growth and development is, let alone what it has to do with nutrition, breast milk and breast milk. This research aims to see the relationship between understanding growth and development with nutritional status, breast milk and breast milk. The respondents were mothers who have toddlers in Tanggeran Village totaling 90 people. Data collection was carried out directly by asking mothers who had children under five. The researcher explains the purpose and objectives of the research in order to solve problems in dealing with toddlers. Information submitted by mothers will be kept confidential and can be used to improve services for toddlers. The research method uses a cross-sectional approach, considering that data collection is carried out simultaneously on mothers who have toddlers. From the results of the research, it was found that 60 people (66.7%) still don't understand the growth and development of mothers under five, 60 people (66.7%) give breast milk when they are 13 to 24 months old, 60 people give breast milk for under 6 months (66.7), and nutritional status according to the KMS. 63 people (70%) are on the green line. The relationship between understanding growth and development with MP-ASI and nutritional status shows that there is a relationship where the Palue p value = 0.0001. What is not related is the understanding of mothers of toddlers with the length of time they provide breast milk, where Palue's p value = 0.417. Thus, it is necessary for mothers of toddlers to understand how to care for them so that they grow into healthy teenagers.